Effects of intercropping on soil fertility and yield of winter wheat - Buriyev Abdivakhab Abdirazzakovich (Peerian Journals Publishing, 2022)
In order to maintain and increase soil fertility in the areas freed from winter wheat, planting of previous crops such as cotton, corn, mung bean, peas, rapeseed and their effect on winter wheat productivity was studied. As a result of the planting of plants that have a positive effect on soil fertility, such as mash, peas, and rapeseed, it was observed that the yield indicators of winter wheat changed in a positive direction
Keywords: previous crop; soil fertility; mung bean; pea